Six new species of Thalassaphorura (Collembola, Onychiuridae) from southern China, with a key to world species of the genus - Sun, Xin; Chen, Jian-Xiu; Deharveng, Louis (Zootaxa, 2010)
The diagnosis of Thalassaphorura Bagnall, 1949 is updated and a key to the world species of the genus is given. Thalassaphorura is recorded for the first time in the Guangxi province, where it is well diversified and usually dominant in Collembola communities. Eight species were collected, including 6 species new to science that are described in this paper (Thalassaphorura bapen sp. nov., T. grandis sp. nov., T. pomorskii sp. nov., T. reducta sp. nov., T. tiani sp. nov. and T. tibiotarsalis sp. nov.) and two widespread species newly recorded from China (T. petaloides and T. encarpata). Half of the species (T. encarpata, T. grandis sp. nov., T. petaloides and T. pomorskii sp. nov.) were only represented by females and are assumed to be parthenogenetic, the four other ones are bisexual.